2001
DOI: 10.1038/sj.pcan.4500517
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lower urinary tract symptoms suggestive of benign prostatic obstruction in real life practice in France

Abstract: The objective of this work is to describe the pro®le of prevalent and incident populations suffering from lower urinary tract symptoms (LUTS) suggestive of benign prostatic obstruction (BPO) and to analyse the management of care by 620 general practitioners (GPs) in France in 1997 and 1998. Patient records were extracted from the THALES database. Special attention was given to the use of medical therapy and switch rates (ie change to another or combination with another drug). In real life practice (RLP) French… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Diagnosis and treatment of LUTS/BPH patients varies significantly worldwide [4][5][6][7][8][9][10][11][12], is independent of the degree of specialization in the subject [5,8], and is considerably influenced by the attending physician's personal and traditional preferences [6,9]. Although this was not an objective of the present study, a similar spread of choices was observed in this particular group of Greek urologists that was indeed independent of age and board certification status.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Diagnosis and treatment of LUTS/BPH patients varies significantly worldwide [4][5][6][7][8][9][10][11][12], is independent of the degree of specialization in the subject [5,8], and is considerably influenced by the attending physician's personal and traditional preferences [6,9]. Although this was not an objective of the present study, a similar spread of choices was observed in this particular group of Greek urologists that was indeed independent of age and board certification status.…”
Section: Discussionsupporting
confidence: 68%
“…Although the European Association of Urology (EAU) has produced guidelines concerning the assessment and treatment of men with BPH, which have been published and updated [1,2], data for the real-life practice concerning the management of this condition are expected to come to light from the ambitious transeuropean research into the use of management policies for LUTS suggestive of BPH in primary healthcare (TRIUMPH) project [3]. Several reports have confirmed differences in the attitude of attending physicians towards the diagnostic tactics and therapeutic strategies for LUTS/BPH [4][5][6][7][8][9][10][11][12] that are independent of the degree of specialization in the subject [5,8], but which are related to the subjectivity of the attending physician and his dependency on traditional preferences [9].…”
Section: Introductionmentioning
confidence: 90%
“…5 In particular, extracts of the American dwarf palm (Serenoa repens, saw palmetto) and blends containing this compound are extremely common treatments for LUTS and are widely available throughout Europe and the USA. 6 Around half of all BPH treatments dispensed in Italy comprise phytotherapeutic agents, and in Austria and Germany such treatments represent over 90% of all BPH drugs dispensed. 7,8 Their use is also rising in the USA, where one-third of men opting for non-surgical treatment report taking phytotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were members of the Thalès network, a representative panel of general practitioners in France who contribute exhaustive anonymous data on patient consultations and treatment to a centralized electronic database, allowing subsequent follow‐up of outcome. The Thalès database has been used widely in previous epidemiological studies 14–18. All 1,010 general practitioners belonging to the network were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%